1988
DOI: 10.1152/ajpheart.1988.255.4.h789
|View full text |Cite
|
Sign up to set email alerts
|

Activity of in vivo canine cardiac plexus neurons

Abstract: The activity of 394 spontaneously active neurons located in the ganglionated plexus of the ventral epicardial fat pad overlying the right atrium and pulmonary veins was recorded. Ganglia that contained various numbers of neurons, many with two or more nucleoli, were identified adjacent to the recording sites. Spontaneous activity was correlated with the cardiac cycle in 39% and with the respiratory cycle in 8% of the identified neurons. Neuronal activity occurred in specific phases of the cardiac cycle when ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 0 publications
4
70
0
Order By: Relevance
“…Originally the intracardiac ganglia were depicted as relay stations where preganglionic and postganglionic parasympathetic neurons synapse (Blomquist et al, 1987). In the past decade it has become evident that these intracardiac ganglionated plexuses contain both cholinergic and adrenergic neurons, as well as interneurons and sensory afferents (Ardell and Randall, 1986;Blomquist et al, 1987;Moravec and Moravec, 1987;Ardell et al, 1988;Gagliardi et al, 1988;Armour and Hopkins, 1990). After removal of all their extracardiac neuronal inputs intracardiac neurons retain their ability for synaptic interactions suggesting that local reflexes may control cardiac dynamics independent of the CNS (Murphy et al, 1994;Armour et al, 1998;Thompson et al, 2000).…”
Section: Nachrs In the Control Of Cardiac Functionmentioning
confidence: 99%
“…Originally the intracardiac ganglia were depicted as relay stations where preganglionic and postganglionic parasympathetic neurons synapse (Blomquist et al, 1987). In the past decade it has become evident that these intracardiac ganglionated plexuses contain both cholinergic and adrenergic neurons, as well as interneurons and sensory afferents (Ardell and Randall, 1986;Blomquist et al, 1987;Moravec and Moravec, 1987;Ardell et al, 1988;Gagliardi et al, 1988;Armour and Hopkins, 1990). After removal of all their extracardiac neuronal inputs intracardiac neurons retain their ability for synaptic interactions suggesting that local reflexes may control cardiac dynamics independent of the CNS (Murphy et al, 1994;Armour et al, 1998;Thompson et al, 2000).…”
Section: Nachrs In the Control Of Cardiac Functionmentioning
confidence: 99%
“…Activity generated by neurons in the RAGP was recorded in situ, as reported previously (3,14). Briefly, to decrease epicardial motion during each cardiac cycle, a circular ring of stiff wire was placed gently on the epicardial fat on the ventral surface of the right atrium-a region known to contain the RAGP.…”
Section: Methodsmentioning
confidence: 99%
“…The activity generated by individual neuronal somata was identified by the amplitude and configuration (waveform recognition) of these recorded action potentials, using the Spike 2 program. By using these techniques and criteria, action potentials generated by individual somata and/or dendrites, rather than axons of passage, can be recorded for extended periods of time (3,4,14).…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary evidence from basic studies 70,71 indicate that the extrinsic autonomic input to the heart, i.e., from the brain and spinal cord, exerts an inhibitory control over the ICANS suggesting www.jafib.comlong term (1 year follow-up) freedom from AF recurrence in 94%. Also, others have reported that drugs that were ineffective prior to GP ablation could be used to maintain sinus rhythm in patients still inducible after GP ablation and PVI .…”
Section: Possible Mechanism Underlying Gp Pathologymentioning
confidence: 99%